SASAK MIGRANT WORKERS: : Slavery, Cultural Challenges, and Family Life During the Migration Period - Saipul Hamdi; Haifazah Awalia; Riska Aini; Sukarman; Ihfan Rahmawadi (Prodi Sosiologi Agama dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2023)
Migrant workers’ lives are filled with drama and social difficulties ranging from enslavement, new cultural obstacles, and social disputes in the places where they work. This article looks at the cultural obstacles that Sasak migrant workers experience in Malaysia, as well as the patterns of slavery that emerge in the workplace. This study was conducted in Suaralaga utilizing qualitative methods and a case study approach. According to the findings, the majority of Indonesian migrant workers face slavery, exploitation, and discrimination in the workplace. They frequently do not receive their salary because the brokers who brought them to the company subtracted and took them. These brokers charge a high fee, resulting in migrant laborers receiving inadequate or no pay at all. Slavery occurs not just in Malaysian enterprises, but it is even more heinous in Indonesian territory when migrant laborers arrive by sea. Although cultural concerns do not pose a problem for migrant employees due to many parallels with Malaysian society, other habits such as consuming beer, free sex, and prostitution in the community surrounding the company make foreign workers uncomfortable. Failure of migrant workers in Malaysia to provide remittances to their families has a significant influence on their family life at home, particularly in meeting the daily necessities of their wives and children